2014
DOI: 10.1111/jth.12736
|View full text |Cite
|
Sign up to set email alerts
|

Impaired thrombin generation in Reelin‐deficient mice: a potential role of plasma Reelin in hemostasis

Abstract: Impaired thrombin generation in Reelin-deficient mice: a potential role of plasma Reelin in hemostasis. J Thromb Haemost 2014; 12: 2054-64.Summary. Background: Reelin is a large extracellular glycoprotein that is present in the peripheral blood. That Reelin interacts with the coagulation components and elicits a functional role in hemostasis has not yet been elucidated. Objectives: The hemostatic activity of Reelin is investigated and defined in this study. Methods: The interplay of Reelin with coagulation com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Reelin, a regulator of brain development and synaptic neuromodulator that signals through ApoE receptors, is also abundant in the liver and present at substantial concentrations in the circulation (21, 23, 24). In the present work, we employed two distinct types of Reelin conditional knockout mice to determine how Reelin affected atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reelin, a regulator of brain development and synaptic neuromodulator that signals through ApoE receptors, is also abundant in the liver and present at substantial concentrations in the circulation (21, 23, 24). In the present work, we employed two distinct types of Reelin conditional knockout mice to determine how Reelin affected atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although atherosclerosis specifically affects arterial vessels, as opposed to the venous system, and is marked by the subendothelial accumulation of lipids and lipid-laden foam cells (40), it shares the recruitment of circulating leukocytes and monocytes to the developing and progressing lesions with other inflammatory processes that involve the vasculature. Reelin has been reported to affect thrombosis and hemostasis (23, 24). Here we have shown that Reelin promotes atherosclerosis by increasing leukocyte adhesion to the vascular endothelium through increased abundance of the major adhesion molecules that are induced during atherogenesis and which promote the accumulation of macrophages in the lesions - ICAM-1, VCAM-1, and E-selectin (34, 35, 41, 42).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations